The distributional product between the finite (formula) in (formula) and (formula) of the k-th derivative of the Dirac delta in hipercono - Aguirre, Manuel A (Nexo Revista Científica, 2013)
Not available DOI: http://dx.doi.org/10.5377/nexo.v25i2.1024